Detection of the presence of Epstein−Barr virus and cytomegalovirus using polymerase chain reaction in patients with chronic kidney disease - Martins, Maria Eduarda Calado Costa; Perez, Mariana de Moraes Corrêa; Dantas, Fernanda Suely Barros; Pessoa, Katarina Haluli Janô da Veiga; Vasconcelos, Luydson Richardson Silva; Melo, Tatiany Patricia Romão Pompilio de; Leão, Jair Carneiro; Carvalho, Alessandra de Albuquerque Tavares (Journal of Oral Diagnosis, 2023)
Background: Chronic kidney disease (CKD) is an advanced and irreversible renal failure that contributes to increased mortality worldwide. Patients who undergo dialysis are more susceptible to developing infections due to their general condition. Epstein-Barr virus (EBV) and Cytomegalovirus (CMV) are associated with oral and systemic manifestations. The most modern and accurate technique to detect the presence of these viruses is polymerase chain reaction (PCR), which can predict viral reactivation even before the onset of symptoms and identify subclinical infections. This study aimed to detect the presence of Epstein-Barr virus (EBV) and Cytomegalovirus (CMV) in patients with chronic kidney disease (CKD) undergoing hemodialysis using real-time polymerase chain reaction (PCR). Methods: An epidemiological and observational case-control study was conducted. Two groups were considered (case group: patients on hemodialysis from the Nephrology Services of the Hospital das Clínicas of UFPE and Hospital Maria Lucinda and control group: healthy patients without CKD from the Department of Stomatology of the UFPE to evaluate the viruses presence using the real-time PCR technique. Results:Of the hemodialysis patients (n=54), 29 (53.70%) tested positive for CMV and only 10 (18.51%) for EBV, while in the healthy group (n=55), eight (14.54%) were positive for EBV and none for CMV. In neither group were systemic characteristics or oral manifestations observed due to the presence of viruses. Conclusion: The EBV and CMV viruses have a higher prevalence in hemodialysis patients. However, these patients did not present oral or systemic manifestations.